Refractive surprise in post-cataract surgery in post Epi-LASIK patient : a lesson learnt - Md Mustafa, Md Muziman Syah; Abdul Mutalib, Haliza; Mohd. Kamal, Khairidzan; Ab. Halim, Noorhazayti (Kulliyyah of Medicine, International Islamic University Malaysia, 2020)
Post-myopic laser refractive surgery corneal power measurement for intraocular lens power calculation is one of the most challenging issues in cataract surgery. Standard keratometry measurement is likely to be overestimated which could lead to false-low intraocular lens power. As a result, this can lead to hyperopic surprise. Contact lens method is an alternative method which is relatively inexpensive and accessible procedure in many optometry and ophthalmology centres. The contact lens method with optimised equations have been used for this case to obtain an accurate postoperative corneal power.